Growth inhibition of cholic acid-conjugated polyethylenimine 25K/ p53-EGFP complexes on human carcinoma cells - Wanlop Weecharangsan, Nattisa Niyomtham, Boon-ek Yingyongnarongkul, Praneet Opanasopit, Robert J. Lee (Journal of Applied Pharmaceutical Science, 2021)
Cholic acid-conjugated polyethylenimine 25K (PEI 25K-CA) was synthesized and characterized for gene delivery of its buffer capacity, PEI 25K-CA/plasmid DNA complex, zeta potential and particle size, transfection efficiency, cytotoxicity, and carcinoma cell growth inhibition. PEI 25K-CA was complexed with plasmid DNA at the ratio above 0.25/1. PEI 25K-CA/p53-EGFP (p53-enhanced green fluorescent protein) and PEI 25K/p53-EGFP had the particle sizes of 238.2 ± 3.1–529.1 ± 3.6 nm, and the zeta potential of 3.7 ± 1.6–4.3 ± 0.2 mV, respectively. The particle size of the complexes increased with the period of time. PEI 25K-CA/p53-EGFP had transfection efficiency as PEI 25K/ p53-EGFP. The cytotoxicity of PEI 25K-CA was dependent on the concentration of the polymer. The growth inhibition activity was dependent on the dose of p53-EGFP. PEI 25K-CA/pEGFP had better colloidal stability than PEI 25K-CA/ pEGFP. This study concluded that PEI 25K-CA had efficient gene delivery activity as PEI and had lower cytotoxicity and more colloidal stability than PEI 25K.
Keywords: Polyethylenimine 25K, cholic acid, p53, gene delivery, cancer.